Stimulasi Literasi Anak Usia Dini Oleh Orang Tua (Systematic Literatur Review) - Wahidah; Formen, Ali; Pranoto, Yuli Kurniawati Sugiyo (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Parental involvement in their children's activities refers to literacy activities where parental behavior interacts with children's literacy learning. The purpose of this study was to identify concepts, target populations, and analysis results that were the focus to clarify the characteristics of studies in previous studies on parental stimulation of early childhood literacy development. The methodology applied was a literature review using the PICO framework, then continued with the selection stage using the PRISMA approach to analyze articles based on inclusion and exclusion criteria from publications in 2015-2024, resulting in 13 articles that were analyzed thematically. Data collection was carried out secondary through online reference sources from Google Scholar, PubMed, and ScienceDirect as part of a comprehensive search. Research results. Parents play a role in early childhood literacy, namely as Modeling, Mentoring, Organizing and Teaching. With literacy skills, namely Print Motivation, Phonological Awareness, Vocabulary, Narrative Skill, Print Awareness and Letter Knowledge. The stimulation carried out includes reading books, interpreting words, naming objects, imitating words, word games, inviting children to buy books, interpreting symbols encountered incidentally, reading writing, introducing letters, interpreting pictures, naming family members, listening to children's stories, asking children's opinions, singing and so on.